Conversational Implicature in the Animated Film Inside Out 2 (2024): A Pragmatic Analysis - Yunus, M. Tegar; Lihawa, Kartin; Saud, Jefriyanto (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This research addresses the research gap concerning how conversational implicatures shift toward context-dependency as characters transition into adolescence. The study aims to identify the types of conversational implicatures and describe the implied meanings conveyed by characters in the animated film Inside Out 2 (2024). Employing a descriptive qualitative design and document analysis, the research applies Grice’s (1975) Cooperative Principle to analyze the film's dialogue. The findings reveal 84 utterances containing conversational implicatures, categorized into 75 Particularized Conversational Implicatures (PCI) and 9 Generalized Conversational Implicatures (GCI). Particularized implicatures were the most dominant, with the Maxim of Quality being the most frequently flouted (56 data). This indicates that adolescent communication in the film is highly sophisticated and context-bound, favoring sarcasm and irony over directness. The study concludes that implied meanings serve critical pragmatic functions, including hiding vulnerability, navigating social hierarchies, and strategic manipulation during the puberty transition.